Iranian Thrips of the Family Aeolothripidae (Insecta, Thysanoptera), with four Newly Recorded Species - Mirab-balou, M.; Chen, X.-X. (Вестник зоологии, 2012)
The family Aeolothripidae (Thysanoptera, Terebrantia) included seventeen species in four genera from Iran. Here, four species are recorded from Iran for the first time: Aeolothrips albicinctus Haliday, A. cursor Priesner, A. montivagus Priesner and A. gloriosus Bagnall. A checklist of all Iranian species of the family Aeolothripidae, with geographical distributions for each species is provided. New distribution records of eight species in Iran are reported. Семейство Aeolothripidae (Thysanoptera, Terebrantia) было известно из Ирана по семнадцати видам из четырех родов. Впервые для фауны Ирана отмечены четыре вида: Aeolothrips albicinctus Haliday, A. cursor Priesner, A. montivagus Priesner и A. gloriosus Bagnall. Приведен список всех иранских видов Aeolothripidae с данными об их географическом распространении. Также приводятся точки новых находок еще восьми видов.